2019
DOI: 10.1083/jcb.201805002
|View full text |Cite
|
Sign up to set email alerts
|

RAB6 and microtubules restrict protein secretion to focal adhesions

Abstract: To ensure their homeostasis and sustain differentiated functions, cells continuously transport diverse cargos to various cell compartments and in particular to the cell surface. Secreted proteins are transported along intracellular routes from the endoplasmic reticulum through the Golgi complex before reaching the plasma membrane along microtubule tracks. Using a synchronized secretion assay, we report here that exocytosis does not occur randomly at the cell surface but on localized hotspots juxtaposed to foca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(140 citation statements)
references
References 41 publications
(84 reference statements)
12
128
0
Order By: Relevance
“…Rab6, a small GTPase interacting with BICD2, is an established regulator of the secretory pathway (Grigoriev et al, 2007;Fourriere et al, 2019) and controls the flow of secreted proteins that are transported from the Golgi to the plasma membrane via a microtubule-dependent process. As a consequence, loss of Rab6 results in a global reduction of protein secretion (Bardin et al, 2015).…”
Section: Patient Fibroblasts Show Evidence Of Impaired Secretionmentioning
confidence: 99%
“…Rab6, a small GTPase interacting with BICD2, is an established regulator of the secretory pathway (Grigoriev et al, 2007;Fourriere et al, 2019) and controls the flow of secreted proteins that are transported from the Golgi to the plasma membrane via a microtubule-dependent process. As a consequence, loss of Rab6 results in a global reduction of protein secretion (Bardin et al, 2015).…”
Section: Patient Fibroblasts Show Evidence Of Impaired Secretionmentioning
confidence: 99%
“…Post-Golgi carriers have also been observed using the "retention using selective hooks" (RUSH) system [59,117]. By fusing a protein of interest to streptavidin-binding peptide (SBP) and coexpressing an ER localised streptavidin, RUSH allows the protein of interest to accumulate in the ER due to the interaction between the streptavidin and the SBP [118].…”
Section: Biosynthetic Lamp1 Carriersmentioning
confidence: 99%
“…Rab6 secretory carriers transport a large variety of cargos. Using the RUSH system, it was shown that Rab6 secretory carriers contain the anterograde cargos CD59, TNFα, and ColX and Rab6 depletion delays the delivery of these cargo to the plasma membrane [117]. Furthermore, Rab6 depletion in embryonic fibroblast cells reduces global protein secretion by 50%.…”
Section: Rab6 Associated Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Microtubules are nucleated at microtubule organizing centers, often the centrosomes, and elongate through sequential phases of growth and shortening, until reaching structures, such as the cell cortex or kinetochores, where they will be captured and stabilized. Microtubule stabilization at the cell cortex is required for oriented trafficking of intracellular vesicles and directed cell motility [1][2][3] . Astral microtubule capture during mitosis is required for mitotic spindle orientation and positioning of the mitotic spindle.…”
Section: Introductionmentioning
confidence: 99%